Spatial Expression and Functional Analysis of Casparian Strip Regulatory Genes in Endodermis Reveals the Conserved Mechanism in Tomato - Li, Pengxue; Yang, Meina; Chang, Jiang; Wu, Junqing; Zhong, Fenglin; Rahman, Abidur; Qin, Haiyang; Wu, Shuang (Frontiers in Plant Science, 2018)
Casparian strip (CS) is an impregnation of endodermal cell wall, forming an apoplastic diffusion barrier which forces the symplastic and selective transport of nutrients across endodermis. This extracellular structure can be found in the roots of all higher plants and is thought to provide the protection of vascular tissues. In Arabidopsis, a genetic toolbox regulating the formation of Casparian strips has emerged recently. However, Arabidopsis has the stereotypical root which is much simpler than most other plant species. To understand the Casparian strip formation in a more complex root system, we examined CS regulatory pathways in tomato. Our results reveal a spatiotemporally conserved expression pattern of most essential components of CS machinery in tomato. Further functional analyses verify the role of homologous CS genes in the Casparian strip formation in tomato, indicating the functional conservation of CS regulatory cascade in tomato.